A Study on the Application of Defect Data Mining in the Aid Decision Making of Dispatching and Control Integration - Guo Hongzuo; Lu Huayong; Su Haitao; Li Lifang; Li Sheng (MATEC Web of Conferences, 2015)
The purpose of the research project is to design an aid decision-making system of dispatching and control integration that cooperates with expert judgments based on the data mining of equipment defects so as to improve the risk pre-warning and pre-control ability of unattended centralized monitoring, enhance the level of centralized monitoring operation and guarantee the safety and stability of power system in the dispatching and control integration system. Defect analysis and condition based maintenance are deeply integrated in this research project. Condition data of equipment defects is firstly obtained and then classified, aggregated and analyzed. Through the model training of SVM, the law of the big data when equipment defects occur is obtained and the operation curve of equipment and the current status information are matched so that the risk of defects can be confirmed and the accuracy of risk anticipation can be effectively improved. In this research project, familial defects of equipment and the expert system are incorporated into the system design range and the practicability of the system is enhanced.